2013
DOI: 10.1186/1475-2891-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients and pregnancy; effect of supplementation on pregnancy and pregnancy outcomes: a systematic review

Abstract: IntroductionEvery year more than 20 million infants are born with low birth weight worldwide. About 3.6 million infants die during the neonatal period. More than one third of child deaths are thought to be attributable to maternal and child under nutrition.ObjectivesTo systematically review the effect of supplementing various combinations and types of micronutrients on the course and outcomes of pregnancy.MethodsElectronic search of Medline, Pub Med, Health Internetwork access to Research Initiative, and Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 20 publications
4
50
0
5
Order By: Relevance
“…It should begin before conception and last at least for the first 12 weeks of pregnancy. The research by Tlałka et al has shown that 8.5% of respondents had never heard the term 'folic acid', and it most often concerned women of lower financial status and education [18]. What has been observed in the present study is the correlation between the levels of education and income of the respondents and the frequency of folic acid intake.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It should begin before conception and last at least for the first 12 weeks of pregnancy. The research by Tlałka et al has shown that 8.5% of respondents had never heard the term 'folic acid', and it most often concerned women of lower financial status and education [18]. What has been observed in the present study is the correlation between the levels of education and income of the respondents and the frequency of folic acid intake.…”
Section: Discussionsupporting
confidence: 68%
“…Badania Tlałka i wsp. wykazały, że 8,5% badanych kobiet w ogóle nie zetknęło się z pojęciem ,,kwas foliowy", dotyczyło to najczęściej kobiet o niższym statusie materialnym i poziomie wykształcenia [18]. W badaniu własnym również obserwujemy korelację pomiędzy wzrostem poziomu wykształcenia i dochodu badanych kobiet a częstością stosowania kwasu foliowego.…”
Section: Discussionunclassified
“…More than one third of child deaths are thought to be attributable to maternal and child under nutrition. Deficiencies in micronutrients such as folate, iron and zinc and vitamins A, B6, B12, C, E and riboflavin are highly prevalent and may occur concurrently among pregnant women 83 . One retrospective study carried out in the department of Gynecology and Obstetrics (Unit-I) of Liaquat University of Medical & Health Sciences Sindh-Pakistan from May 2011 to May 2012 showed that among (n=1225) pregnant women, 688 were anemic (Hb < 11g/dl) prevalence of anemia was 56.1%.…”
Section: Infant Mortality and Morbiditymentioning
confidence: 99%
“…In our study 25.7% of pregnant women their hemoglobin were less than 9 /dL. According to the WHO'S, iron and folic acid are recommended to reduce the risk of iron deficiency anemia, which is prevalent among pregnant ladies [17]. Fetal birth weight is directly proportional to maternal health and nutritional status.…”
Section: Discussionmentioning
confidence: 97%